2020
DOI: 10.1108/rpj-03-2019-0082
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cation exchange filament for 3D membrane print

Abstract: Purpose This paper aims to focus on the preparation of a cation exchange filament for three-dimensional (3D) fused deposition modeling (FDM). The polymeric binder was mixed with the selected conventional cation exchange resin and a filament was prepared using a mini extruder. Filaments were tested by mechanical properties, chemical properties, quality and melt flow index. Samples were prepared from granulate using a press, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Furthermore, 3D printing of hydrogels exhibits some compelling features. H. Baniasadi et al reported 3D printed hydrogels that showed a very high porosity with open and interconnected pores which allowed for a high-water uptake capacity (up to 1600%) [ 171 ]. Composite 3D-printed materials open options for skin wound dressing applications due to their mechanical strength that is comparable to that of soft tissues.…”
Section: Recent Developments In the 3d Printing Of Hydrogel Wound Dre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 3D printing of hydrogels exhibits some compelling features. H. Baniasadi et al reported 3D printed hydrogels that showed a very high porosity with open and interconnected pores which allowed for a high-water uptake capacity (up to 1600%) [ 171 ]. Composite 3D-printed materials open options for skin wound dressing applications due to their mechanical strength that is comparable to that of soft tissues.…”
Section: Recent Developments In the 3d Printing Of Hydrogel Wound Dre...mentioning
confidence: 99%
“…Composite 3D-printed materials open options for skin wound dressing applications due to their mechanical strength that is comparable to that of soft tissues. Drug-loaded dressings demonstrated controlled and efficient delivery of the antioxidant, ascorbic acid, in phosphate-buffered saline (PBS) at 23 °C, where 80% of the loaded drug was released within 8 h [ 171 ]. The experimental findings indicated a correlation among shrinkage, porosity, pore size, and the swelling ratio of the dressings.…”
Section: Recent Developments In the 3d Printing Of Hydrogel Wound Dre...mentioning
confidence: 99%